Gender Minority Status and Family Inequality in the United States - Christopher S. Carpenter; Maxine J. Lee; Laura Nettuno (RSF: The Russell Sage Foundation Journal of the Social Sciences)
We provide new evidence on marital status and family outcomes of transgender and other gender minority populations in the United States using more than fifteen thousand non-cisgender adults in the Census Bureau’s 2021–2023 Household Pulse, the only nationally representative survey in the United States with information on sex at birth and current gender. These data indicate that non-cisgender individuals—those whose sex at birth does not align with their current gender—are significantly less likely to be married and more likely to have a spouse who has passed away than their cisgender counterparts. Non-cisgender individuals are also significantly less likely than otherwise similar cisgender women to have children in the household. Non-cisgender individuals live in households with significantly more adults than otherwise similar cisgender adults.